Utilisation of Innovative Technology towards a Human-Centred Future Society - Verma, Pushp Lata (SCHOOL SCIENCE, 2017)
India views technology and digitisation as essential tools to advance towards a scenario in which citizens and the challenges they encounter are placed at the centre of technological innovation, solution development, and service delivery. With a firm foundation of digital infrastructure and expanded digital access through Digital India Programme, India is now poised for the next phase of growth, creating tremendous economic value and empowering citizens as new technological applications permeate every sector. India has successfully leveraged the amalgamation of various platforms, such as PMJDY, AADHAAR, mobile phones (Mobile) and their links with public cloud (Meghraj), Digilocker, UPI/BHIM, AEPS, JAM. In addition, digital transformation in India has successfully bridged the gender divide by increasing women inclusion in employment, school enrolment for girls, admission in BPO training programmes and in supporting women entrepreneurs and self-help groups for showcasing their products and services, therefore catalysing numerous opportunities for women. This article sheds light on such initiatives and their benefits and discusses overall utilisation of innovative technology towards a human-centred future society.